Optimal design of BiCMOS second generation current conveyor using the genetic algorithm - El Beqal Asmae; Benhala Bachir; Zorkani Izeddine (Institute of Advanced Engineering and Science, 2023)
This article presents an innovative implementation of the plus-type second-generation current conveyor (CCII+) using BiCMOS technology, which combines the benefits of bipolar and CMOS technologies. The optimization problem of minimizing the X-port input resistance and maximizing the current cut-off frequency value was solved using genetic algorithm (GA). The proposed approach allows the optimization of the BiCMOS CCII+ to achieve better performance compared to previous designs. As a practical application, a second-order band-pass filter using the optimized BiCMOS CCII+ was successfully realized. The performance of the proposed design was evaluated using SPICE simulations and compared with previously published works. This study shows that the BiCMOS CCII+ can be effectively optimized using GA to improve its performance, which has potential applications in various analog and mixed-signal circuits.